Fabrication of microwave-absorbing MFe2O4@sepiolite (M = Mn, Mn0.5Ni0.5, Ni) nanorods with enhanced catalytic performance for degradation and assessment of intermediate toxicity - Ruolin Ni; Lei Jiang; Jinhui Lin; Dan Wu; Keming Zhang; Lu Fu; Zhaohong Zhang; Fang Ma; Yongcai Zhang (Applied Clay Science, 2026)

Chronic exposure to Bisphenol AF from gestation through adulthood induces renal injury in 8-month-old mice via lipid metabolism dysregulation and ferroptosis - Rui Gao; Jiangsong Ma; Aonan Lu; Xiaoyun Wu; Chao Zhang; Keming Yun; Zhe Chen; Xiaotong Ji (Journal of Hazardous Materials, 2026)

Comparative Transcriptome and Gene-Editing Analyses Reveal the Molecular Mechanism of Albinism in the Taiwanese Loach - Rongyun Li; Xiaohui Bai; Xiaojuan Cao; Shuang Hao; Keming Liu; Zhang Luo; Jian Gao; Yaoxin Wang; Yunbang Zhang; Lin Ma; Jufeng Jiang (Marine Biotechnology, 2026)

From protein-like to humic-like substances: Feed-derived regulation of dissolved organic matter transformation in RAS - Ying Bai; Ruijie Ma; Zhengguo Cui; Hao Li; Hongwu Cui; Yong Xu; Jianlei Chen; Keming Qu (Aquacultural Engineering, 2026)

Unveiling the mechanism: DOM from chemically pretreated corncobs drives denitrification via mediating microbial community succession - Ying Bai; Ruijie Ma; Zhengguo Cui; Hongwu Cui; Weiman Gong; Wei Dong; Hao Li; Yong Xu; Jianlei Chen; Keming Qu (Journal of Environmental Chemical Engineering, 2026)

How does vegetation invasion reshape bird communities? Insights from mangrove and Spartina alterniflora saltmarsh in coastal China - Qingyan Sun; Xueman Xing; Keming Ma (Journal of Environmental Management, 2026)

Modeling and analysis of electromagnetic, fluid and energy characteristics in flat linear induction pump - Sixian Zhu; Jien Ma; Zheng Wang; Keming Bi; Xin Yan; Youtong Fang (Annals of Nuclear Energy, 2026)

Exploring dynamic habitat compensation through waterbird responses to paddy field landscapes - Xueman Xing; Keming Ma; Fawen Qian (Journal of Environmental Management, 2026)

Restoring plant diversity on Loess Plateau mining slopes: effects of artificial soil and slope characteristics with management strategies - Zhang Chen; Oumeng Qiao; Keming Ma; Ziqiang Du (Journal of Environmental Management, 2025)

Modeling and optimization of planar induction electromagnetic pump based on genetic algorithm mixed with parameter sweep - Wenxiao Wu; Jien Ma; Keming Bi; Xin Yan; Youtong Fang (Annals of Nuclear Energy, 2025)

Sedimentary heavy metal interactions with phytoplankton and zooplankton across the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Environmental Management, 2025)

Context dependence masks the long-term harm of Spartina alterniflora invasion on macrobenthos in China - Qingyan Sun; Keming Ma (Journal of Environmental Management, 2025)

Ecological risk assessment for BDE-47 in marine environment based on species sensitivity distribution method - Ying Bai; Ruijie Ma; Zhengguo Cui; Liping Liu; Dongsheng Ding; Qingjing Hu; Bin Xia; Zhaochuan Li; Haibo Zhang; Keming Qu (Marine Environmental Research, 2025)

A novel hybrid model for annular linear induction pump - Sixian Zhu; Jien Ma; Keming Bi; Xin Yan; Youtong Fang (Annals of Nuclear Energy, 2025)

Building ecosystem services-based ecological networks in energy and chemical industry areas - Huanhuan Pan; Ziqiang Du; Zhitao Wu; Hong Zhang; Keming Ma (Ecological Modelling, 2024)

A study of the pharmacokinetics of clozapine and its metabolites by the dynamics of its distribution in the oral fluid of healthy volunteers - Qianwen Shi; Lele Wang; Qian Zheng; Yefei Pan; Xiaohui Tan; Yao Liu; Shanlin Fu; Ande Ma; Zhiwen Wei; Keming Yun (Archives of Toxicology, 2024)

Implications of ocean warming and acidification on heavy metals in surface seawater of the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Hazardous Materials, 2024)

Soil application of graphitic carbon nitride nanosheets alleviate cadmium toxicity by altering subcellular distribution, chemical forms of cadmium and improving nitrogen availability in soybean (Glycine max L.) - Kai Xu; Lifan Zheng; Kaifei Chu; Chenghua Xing; Jiajing Shu; Keming Fang; Shuting Ma; Yong Fang; Jianfang Yan; Miaozhen Cai; Xi-Lin Wu (Journal of Environmental Management, 2024)

Interplays between plants and environmental factors determine pullout resistance on different revegetated slopes in mining areas - Zhang Chen; Oumeng Qiao; Yong Liu; Keming Ma; Huiping Song; Chengjun Li (Journal of Environmental Management, 2024)

Effect of enzyme-assisted fermentation on quality, safety, and microbial community of black soldier fly larvae (Hermetia illucens L.) as a novel protein source - Leying Meng; Liangxiao Ma; Jiahui Xu; Keming Rong; Nan Peng; Shumiao Zhao (Food Research International, 2023)

Hydrocarbons removal and microbial community succession in petroleum-contaminated soil under hydrogen peroxide treatment - Bing Yang; Mi Zhou; Yuan Meng; Keming Chen; Jie Xu; Xiangfu Huang; Yucheng Liu; Lingli Li; Lili Ma; Mingyan Chen (Environmental Science and Pollution Research, 2022)

Identifying changing interspecific associations along gradients at multiple scales using wavelet correlation networks - Zhangqi Ding; Keming Ma (Ecology, 2021)
Identifying interspecific associations is very important for understanding the community assembly process. However, most methods provide only an average association and assume that the association strength does not vary along the environmental gradient or with time. The scale effects are generally ignored. We integrated the idea of wavelet and network topological analysis to provide a novel way to detect nonrandom species associations across scales and along gradients using continuous or presence–absence ecological data. We first used a simulated species distribution data set to illustrate how the wavelet correlation analysis builds an association matrix and demonstrates its statistical robustness. Then, we applied the wavelet correlation network to a presence–absence data set of soil invertebrates. We found that the associations of invertebrates varied along an altitudinal gradient. We conclude by discussing several possible extensions of this method, such as predicting community assembly, utility in the temporal dimension, and the shifting effects of highly connected species within a community. The combination of the multiscale decomposition of wavelet and network topology analysis has great potential for fostering an understanding of the assembly and succession of communities, as well as predicting their responses to future climate change across spatial or temporal scales.

Foliar Particulate Matter Distribution in Urban Road System of Beijing, China - Le Bao; Keming Ma; Xiaowu Xu; Xinxiao Yu (Chinese Geographical Science, 2019)

A trait‐based approach reveals the importance of biotic filter for elevational herb richness pattern - Zihan Jiang; Keming Ma; Hongyan Liu; Zhiyao Tang (Journal of Biogeography, 2018)
Aim To evaluate how a biotic filter (overstorey cover [ OC ]) shapes an elevational herb richness pattern and to test whether intermediate elevations represent more suitable habitats for herb species due to the minimal biotic and moderate abiotic filtering that occured there. Location Dongling Mountain, China. Taxon Herbs. Methods We sampled herb richness along a 1,000‐m vertical transect ( OC and elevation covary) and four horizontal transects (across the OC gradient with no change in elevation). Functional traits related to shade (leaf mass per area [ LMA ] and leaf stem ratio [ LSR ]) and freezing tolerance (leaf thickness [ LT ] and hair density [ HD ]) were collected based on vegetation sampling plots. We divided the richness data into below‐ and above‐timberline groups and then assessed the most important driver for each group. By estimating the variations in species richness and functional diversity along horizontal transects, we examined how these parameters responded to OC while controlling for associated differences in elevation. Results Herb richness showed a unimodal relationship with elevation, with a peak around the timberline. Below the timberline, herb richness was better predicted by OC and showed a positive relationship with the functional diversity of LMA and LSR . The frost period performed better in predicting herb richness above the timberline, and herb richness was positively related to the functional diversity of HD . Main conclusions The results support our hypothesis and highlight the importance of OC in shaping herb richness patterns. Below the timberline, OC acts as a filter, sorting species based on their ability to tolerate shade, whereas the frost period limits richness above the timberline and favours species that can tolerate low temperatures. Therefore, we suggest that biotic interactions, as well as environmental and geographical factors, should be considered the main drivers of elevational plant richness patterns.

Consumption of an exotic plant (Spartina alterniflora) by the macrobenthic fauna in a mangrove wetland at Zhanjiang, China - Quan Chen; Guorui Xu; Shuang Zhang; Keming Ma (Wetlands, 2018)

Effects of plant coverage on shrub fertile islands in the Upper Minjiang River Valley - Laiye Qu; Zhongbin Wang; Yuanyuan Huang; Yuxin Zhang; Chengjun Song; Keming Ma (Science China Life Sciences, 2018)

Altitudinal variation in ant–aphid mutualism in nitrogen transfer of oak (Quercus liaotungensis) - Limin Zhang; Yuxin Zhang; Naiqing Fan; Shuang Zhang; Keming Ma; Shukui Niu (Arthropod-Plant Interactions, 2017)

PtrMYB57 contributes to the negative regulation of anthocyanin and proanthocyanidin biosynthesis in poplar - Shuzhen Wan; Chaofeng Li; Xiaodong Ma; Keming Luo (Plant Cell Reports, 2017)

The association of leaf lifespan and background insect herbivory at the interspecific level - Shuang Zhang; Yuxin Zhang; Keming Ma (Ecology, 2017)
Herbivory is well known to be a major selective pressure that affects plant communities, but the leaf traits that mediate variations in herbivory at the interspecific level remain controversial. We collected published data on background insect herbivory and leaf traits from a wide variety of species to test the hypothesis that species with intermediate leaf lifespans, lower fiber, and higher nutrient contents in leaves should have higher levels of herbivory. We found that at the interspecific level herbivory had a hump‐shaped relationship with leaf lifespan and a positive relationship with leaf size. Surprisingly, our data show that nutritional traits have little relationship to herbivory. Our study provides new insights relevant to the recent debate on leaf trait–herbivory relationships. These findings are especially helpful in explaining the general patterns of herbivory detected on the global scale.

Contrasting elevational diversity patterns for soil bacteria between two ecosystems divided by the treeline - Guixiang Li; Guorui Xu; Congcong Shen; Yong Tang; Yuxin Zhang; Keming Ma (Science China Life Sciences, 2016)

Can the physiological tolerance hypothesis explain herb richness patterns along an elevational gradient? A trait-based analysis - Zihan Jiang; Keming Ma; M. Anand (Community Ecology, 2016)

Interplay of temperature and woody cover shapes herb communities along an elevational gradient in a temperate forest in Beijing, China - Zihan Jiang; Keming Ma; M. Anand; Yuxin Zhang (Community Ecology, 2015)

Carbon and nitrogen isotopes analysis and sources of organic matter in surface sediments from the Sanggou Bay and its adjacent areas, China - Bin Xia; Yi Cui; Bijuan Chen; Zhengguo Cui; Keming Qu; Feifei Ma (Acta Oceanologica Sinica, 2014)

Comparison on soil carbon stocks between urban and suburban topsoil in Beijing, China - Shanghua Luo; Qizheng Mao; Keming Ma (Chinese Geographical Science, 2014)

Soil microbial properties under different vegetation types on Mountain Han - Miao Wang; LaiYe Qu; KeMing Ma; Xiu Yuan (Science China Life Sciences, 2013)

Distribution pattern of allergenic plants in the Beijing metropolitan region - Qizheng Mao; Keming Ma; Jianguo Wu; Rongli Tang; Shanghua Luo; Yuxin Zhang; Le Bao (Aerobiologia, 2013)

Partitioning the effects of environmental and spatial heterogeneity on distribution of plant diversity in the Yellow River Estuary - Xiu Yuan; KeMing Ma; De Wang (Science China Life Sciences, 2012)

Different-sized oak trees are equally protected by the aphid-tending ants - Shuang Zhang; Yuxin Zhang; Keming Ma (Arthropod-Plant Interactions, 2012)

Seasonal dynamics of nitrogen and phosphorus in water and sediment of a multi-level ditch system in Sanjiang Plain, Northeast China - Lei Guo; Keming Ma (Chinese Geographical Science, 2011)

Wetland loss under the impact of agricultural development in the Sanjiang Plain, NE China - Jieyu Zhang; Keming Ma; Bojie Fu (Environmental Monitoring and Assessment, 2010)

Testing a Dynamic Complex Hypothesis in the Analysis of Land Use Impact on Lake Water Quality - QingHai Guo; KeMing Ma; Liu Yang; Kate He (Water Resources Management, 2010)

Vascular plant species richness on wetland remnants is determined by both area and habitat heterogeneity - Jianmin Shi; Keming Ma; Jifeng Wang; Jingzhu Zhao; Kate He (Biodiversity and Conservation, 2010)

Entangling the Complexity of Protected Area Management: The Case of Wolong Biosphere Reserve, Southwestern China - Bojie Fu; Kelin Wang; Yihe Lu; Shiliang Liu; Keming Ma; Liding Chen; Guohua Liu (Environmental Management, 2004)